Reimagining Hammarkullen adaptive reuse of a basement through urban commons and spatial justic - Koshy Jacob, Nithin (My University, 2025)
This thesis explores how neglected urban infrastructures can be reimagined as urban commons to advance social sustainability, spatial justice, and community resilience. Taking an abandoned basement parking facility in Hammarkullen, Gothenburg, as its test case, the study challenges prevailing demolition-oriented planning logics and examines adaptive reuse as a socially and environmentally responsible alternative. Grounded in the theoretical frameworks of urban commons and spatial justice, and supported by concepts of adaptive reuse, resilience, and socio-technical systems, the research combines spatial and contextual analysis, policy review, interviews with local stakeholders, and insights from case studies. The design approach emphasizes incremental transformation, collective governance, and the integration of productive systems such as hydroponics. While the project is site-specific, it offers a broader provocation: that neglected infrastructures, often dismissed as liabilities, can be repositioned as infrastructures of inclusion and resilience. In doing so, the thesis suggests pathways for architectural and urban practice that extend beyond technical solutions toward socially anchored transformation
Keywords: Urban Commons; Spatial Justice; Adaptive Reuse; Resilience; Hydroponics; Socio-Technical Systems; Circular Economy; Hammarkullen